Trade and investment barriers affecting international production networks in India - Anwarul Hoda; Durgesh Kumar Rai (Indian Council for Research on International Economic Relations (ICRIER), 2014)
This paper analyses the reasons behind India lagging behind East and South East Asian economies in participating in international production networks, on which growth in manufacturing has become increasingly dependent in the contemporary world. Since multinational firms are the main coordinating agents in these networks, whether through affiliates or procurement of in puts through arm's length transactions, the paper examines the reasons for India's inability to attract foreign investment in manufacturing. It examines in particular the role played by logistics infrastructure and processes in the selection by investors of particular locations for investment in manufacturing. The paper also lists out other shortcomings in the domestic investment environment that have made India less attractive for foreign as well as domestic investors in comparison with East and South East Asian countries. A feature of the analytical framework adopted is comparison of the situation prevailing in India with that in three comparator countries, viz., China, Malaysia and Thailand with respect to logistics and other factors that determine the investment environment, so as to enable an assessment of the scale and direction of effort needed to bring India on par with these countries.
Keywords: F13; F21; L23; L24; L52; 330; International Production Sharing; FDI; Outsourcing; Trade Barriers; Logistics